2021
DOI: 10.1002/saj2.20332
|View full text |Cite
|
Sign up to set email alerts
|

Apparent kinetic properties of soil phosphomonoesterase and β‐glucosidase are disparately influenced by pH

Abstract: Extracellular enzymes catalyze organic matter transformations in soils, yet the study of soil enzymes does not typically evaluate how enzyme kinetic properties that govern activity in situ may shift with environmental parameters such as pH. To test this, we quantified changes in apparent kinetic properties (maximum catalysis rate [AppVmax] and substrate concentration that produces 50% of Vmax [AppKm]) of soil phosphomonoesterase (PME) and β‐glucosidase (BG) as a function of pH by using dual gradients of buffer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Visualizing enzyme activity as a function of pH—appropriate for many soil × enzyme combinations for which there is not a clear “peak” of maximum activity—qualitatively points to the relative importance of enzyme type over soil land use or management. Though relatively similar pH optima among long‐term soil land uses and managements may reflect in part the relatively constrained pH of our soils (pH 6.2–7.4) (Puissant et al., 2019), fine‐scale alteration of pH–activity relationships could also reflect isozyme variability (Li & Margenot, 2021; Wade et al., 2021). Our results suggest that at in situ environmental (i.e., soil) pH, enzyme activities will not catalyze hydrolysis of N‐substrates at maximum rates to the extent that enzyme activity pH optima are not aligned with soil pH.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Visualizing enzyme activity as a function of pH—appropriate for many soil × enzyme combinations for which there is not a clear “peak” of maximum activity—qualitatively points to the relative importance of enzyme type over soil land use or management. Though relatively similar pH optima among long‐term soil land uses and managements may reflect in part the relatively constrained pH of our soils (pH 6.2–7.4) (Puissant et al., 2019), fine‐scale alteration of pH–activity relationships could also reflect isozyme variability (Li & Margenot, 2021; Wade et al., 2021). Our results suggest that at in situ environmental (i.e., soil) pH, enzyme activities will not catalyze hydrolysis of N‐substrates at maximum rates to the extent that enzyme activity pH optima are not aligned with soil pH.…”
Section: Discussionmentioning
confidence: 96%
“…That soil pH and enzyme activity pH optima are not necessarily aligned raises questions on our understanding of soil enzyme activities (Wade et al., 2021), as it would be expected the pH optima would reflect soil pH in order to maximize the catalytic efficiency of extracellular enzymes (Puissant et al., 2019). On the other hand, evolutionary entrenchment of pH optima due to active site and other protein structure constraints may limit pH optima of enzymes originally evolved in different pH environments (e.g., intracellular or constrained extracellular pH ranges) that are now secreted as extracellular enzymes into the soil environment (Li & Margenot, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Forest‐to‐pasture conversion at our site entailed shifts in soil microbial community structure (Paula et al., 2014; Rodrigues et al., 2013), which may have altered isoenzyme composition and thus kinetic properties of the soil extracellular enzyme pool (Farrell et al., 1994; Khalili et al., 2011; Tabatabai et al., 2002). The K a normalizes the V max to K m as a metric of catalytic efficiency (Esti et al., 2011; Li & Margenot, 2021; Stone & Plante, 2014). Increases in K a of both PME and PDE with pasture age suggested that in older pastures, the microbial–plant consortium shifted to the production of phosphates with greater catalytic efficiency than in younger pastures or primary forests.…”
Section: Discussionmentioning
confidence: 99%
“…For example, “activities of acid and alkaline phosphatase” are defined by the method used to assay their activity, with buffer at pH 6.5 and 11.0, respectively. In reality, a given soil exhibits activity of phosphomonoesterase (PME) in unpredictable patterns across the pH continuum (e.g., Li & Margenot, 2021; Puissant et al., 2019; Turner, 2010)—a basic principle well‐recognized in enzymology (Bisswanger, 2014) but largely absent in soil enzyme activity assays (Wade et al., 2021). Most enzymes do not “mineralize” nutrient elements : Mineralization is the last step of converting an organic form of a nutrient element to an inorganic form.…”
mentioning
confidence: 99%